A practical guide to outcome evaluation - Hoggarth, Liz (Jessica Kingsley Publishers, 2010)
In the current climate of planning and commissioning services, the need for statutory, voluntary and even private sector projects to understand how to evaluate and present the outcomes of their work is unavoidable. From fundraising for an outreach dance education scheme, to smoking cessation programmes offered by health professionals, this versatile 'how to' book will help you evaluate results and make the most of your project. This practical handbook on how to evaluate outcomes in people-orientated projects will support decision making and lead to better communication, improved funding applic.